Importance of extracardiac alpha(1)-adrenoceptor stimulation in assisting dofetilide to induce torsade de pointes in rabbit hearts - Farkas Attila; Acsai Károly; Tóth András; Dézsi László; Orosz Szabolcs; Forster Tamás; Csanády Miklós; Papp Gyula; Varró András; Farkas András (2006)
In anaesthetized rabbits, alpha(1)-adrenoceptor stimulation increases the propensity of repolarization-prolonging drugs to induce torsade de pointes ventricular tachycardia. However, it is not known whether the stimulation of intracardiac alpha(1)-adrenoceptors, or the increased ventricular stretch caused by extracardiac alpha(1)-adrenoceptor-mediated peripheral vasoconstriction and increased resistance, are the sensitizing factors. Accordingly, this study investigated whether a sustained load-induced left ventricular stretch or stimulation of the intracardiac alpha(1)-adrenoceptors with 100 nM methoxamine, or the co-application of these two, can assist dofetilide (100 nM) to elicit torsade de pointes in isolated Langendorff-perfused, rabbit hearts. In the stretched hearts, a constant high level of stretch was produced by a water-filled left ventricular balloon inflated to a volume of 1.4 ml, whereby the systolic and end-diastolic pressures virtually did not exceed the physiological range (<= 157 +/- 11 mm Hg and <= 9 +/- 2 min Hg, respectively; mean +/- S.E.M.). Perfusion with dofetilide prolonged the QT interval significantly and indifferently in all hearts. Neither this stretch nor methoxamine nor the in combination affected the QT interval, the heart rate or the coronary flow. Interestingly, neither the stretch ('dofetilide+ stretch' group, n=8 hearts), nor methoxamine ('dofetilide+methoxamine' group, n=8 hearts), nor the in combination ('dofetilide+stretch+ methoxamine' group, n=8 hearts) elevated the incidence of torsade de pointes as compared with the 'dofetilide alone' group (n=9 hearts) (0%, 25%, 0%, versus 44%, respectively). In conclusion, neither a sustained load-induced stretch nor alpha(1)-adrenoceptor stimulation nor the in combination assisted dofetilide to induce torsade de pointes in isolated rabbit hearts, suggesting the importance of extracardiac alpha(1)-adrenoceptor stimulation in this phenomenon. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Általános orvostudomány